A TiAlMoN / TiAlTaN composite coating for steel processing and its preparation method
By introducing Mo and Ta elements into the TiAlN coating to form a multi-layer TiAlMoN/TiAlTaN composite coating, the problem of hardness loss of the TiAlN coating at high temperatures is solved, high wear and heat resistance cutting performance is achieved, and the service life and processing effect of the tool are improved.
Patent Information
- Application Number
- CN202311229119.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-09-26
- Estimated Expiration
- 2043-09-21
AI Technical Summary
The hardness of existing TiAlN coatings decreases during high-speed cutting and dry cutting, and their high-temperature wear resistance is insufficient, resulting in strong adhesion of the tool when processing difficult-to-cut materials such as stainless steel, affecting processing accuracy and speed.
TiAlMoN/TiAlTaN composite coating is used. By introducing Mo and Ta elements to form a multilayer structure and combining with multi-arc ion plating technology, a highly wear-resistant and heat-resistant coating is prepared. The high wear resistance of Mo and the high thermal stability of Ta are utilized to improve the bonding strength and oxidation resistance of the coating.
It significantly improves the hardness and high-temperature stability of the coating, enhances the wear resistance and oxidation resistance of the tool, extends the tool life, and improves processing efficiency and precision.
Smart Images

Figure CN117026173B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings for cutting tools, and in particular to a TiAlMoN / TiAlTaN composite coating for steel processing and a preparation method thereof. Background Art
[0002] In recent decades, the market demand for cutting tools has continued to rise, driving the rapid development of tool coatings. Modern manufacturing places higher demands on machining processes, and the need for improved efficiency, reliability, and precision has led to a growing interest in tool coating technology. Coatings act as chemical and thermal barriers, preventing direct contact between the tool and the workpiece and reducing interdiffusion between the tool and the workpiece. This improves the tool's resistance to oxidation, adhesion, and abrasive wear, ultimately increasing tool life, cutting efficiency, and workpiece surface quality. Furthermore, tool coatings offer considerable versatility; one coated tool can replace several uncoated tools, offering a wide range of applications. Coated tools also facilitate dry cutting, eliminating the increased production costs associated with the use and disposal of cutting fluids, and reducing environmental pollution and worker health hazards.
[0003] TiAlN coating is currently the most widely used protective coating for cutting tool surfaces. In terms of mechanical properties, its hardness reaches up to 30GPa due to the formation of a (Ti,Al)N solid solution. In terms of oxidation resistance, during the high-temperature oxidation process, the Al element oxidizes to form a continuous and dense Al2O3, which effectively blocks the inward diffusion of the O element and slows down the oxidation process. However, during high-speed cutting and dry cutting, the tool edge temperature can exceed 1000°C, exceeding the operating temperature of the TiAlN coating, and its hardness drops to below 1200HV, significantly reducing its high-temperature wear resistance. Especially when machining difficult-to-cut materials such as stainless steel at high temperatures, these materials, due to their strong adhesion and high hardness, easily form a large amount of built-up edge on the tool surface, seriously affecting the machining accuracy and speed. Obviously, a single TiAlN coating cannot meet the machining requirements. Multi-element doping and composite coatings have become the only choice for the new generation of coating technologies and have attracted the attention of more and more researchers. Summary of the Invention
[0004] Purpose of the invention: In order to address the deficiencies in the prior art, the present invention aims to provide a TiAlMoN / TiAlTaN composite coating for steel processing that has good substrate matching, long service life, and is wear-resistant and high-temperature resistant. In addition, the present invention also provides a method for preparing the TiAlMoN / TiAlTaN composite coating for steel processing.
[0005] Technical solution: The TiAlMoN / TiAlTaN composite coating for steel processing of the present invention comprises a Ti bonding layer, a TiN transition layer and a TiAlMoN / TiAlTaN functional layer, wherein the TiAlMoN / TiAlTaN functional layer is composed of (TiAl) 1-x Mo x N layer and (TiAl) 1-y Ta y It is composed of N layers, wherein x: 2-20 at.%, y: 2%-15 at.%, and x+y: 5%-30 at.%.
[0006] Furthermore, the thickness of the Ti bonding layer is 50-100 nm, the thickness of the TiN transition layer is 200-600 nm, and the thickness of the TiAlMoN / TiAlTaN functional layer is 1-6 μm.
[0007] The method for preparing the TiAlMoN / TiAlTaN composite coating for steel processing according to the present invention comprises the following steps:
[0008] (1) Pretreatment of the substrate;
[0009] (2) Place the substrate on the rotating rack of the multi-arc ion coating machine and start the vacuuming process;
[0010] (3) Turn on the heater;
[0011] (4) Turn on the filament power supply, introduce argon gas, maintain vacuum, set the DC power supply voltage and current to perform glow cleaning on the substrate;
[0012] (5) Open the Ti target, introduce argon, maintain vacuum, and plate the Ti bonding layer;
[0013] (6) Turn on the Ti target, turn off the argon gas, introduce nitrogen, maintain the vacuum, and plate the TiN transition layer;
[0014] (7) Opening the TiAlMo target and the TiAlTa target, introducing nitrogen, and depositing the TiAlMoN layer and the TiAlTaN layer simultaneously to form a TiAlMoN / TiAlTaN functional layer;
[0015] (8) Turn off the TiAlMo target and the TiAlTa target, turn off the nitrogen and the heater, and take them out of the furnace after cooling to obtain the TiAlMoN / TiAlTaN composite coating for steel processing.
[0016] Furthermore, in step (2), the substrate is high-speed steel or cemented carbide; the speed of the rotating rack is 1-4 r / min, and the vacuum degree after vacuuming is (1-5)×10 -2 Pa.
[0017] Furthermore, in step (3), the heating temperature is 300-500°C.
[0018] Furthermore, in step (4), the flow rate of the argon gas is 20-70 sccm, the DC power supply voltage is 30-60 V, the current is 10-20 A, and the glow cleaning time is 30-90 min.
[0019] Furthermore, in step (5), the parameters of the Ti bonding layer are: arc current of 30-50A, bias voltage of 600-800V, and deposition time of 2-6min.
[0020] Furthermore, in step (6), the flow rate of the nitrogen gas is 130-180 sccm; the parameters of the TiN transition layer are: arc current is 40-70A, duty cycle is 20-80%, bias voltage is 200-300V, and deposition time is 5-15min.
[0021] Furthermore, in step (7), the parameters of the TiAlMoN / TiAlTaN functional layer are: arc current of 80-120A, duty cycle of 60-90%, bias voltage increased from 10-50V to 100-200V, substrate bias voltage linear increase ratio of 0.5-3, deposition time of 40-80min; in the TiAlMo alloy target and TiAlTa alloy target, the atomic percentage ratio of Ti:Mo is 40%-60%:2%-10%, and the atomic percentage ratio of Ti:Ta is 40%-60%:2%-10%; the ventilation of the target material is achieved by drilling holes around the evaporation source, wherein the number of holes in the TiAlMo evaporation source flange is 3-8, and the number of holes in the TiAlTa evaporation source flange is 3-8.
[0022] Principle of the invention: In order to solve the problems of strong adhesion, low high-temperature hardness, and severe local wear of existing cutting tools during steel processing, the present invention provides a highly wear-resistant and heat-resistant TiAlMoN / TiAlTaN composite coating, which is achieved by introducing Mo and Ta elements into the coating as solid solutions. Due to the solid solution strengthening effect of Mo and Ta elements, the hardness of the composite coating is significantly improved. The multi-layer structural design interrupts the growth of columnar crystals, prevents the spread of cracks, and improves the bonding strength of the coating. By doping with Mo elements, the cutting force, the temperature during the cutting process, and the contact area can be changed, thereby improving the friction performance of the coating. Ta elements are doped on the TiAlMoN coating to form a TiAlTaN coating, because Ta elements promote the direct formation of α-Al2O3 and stable γ-TiO2 phases at high temperatures. At the same time, combined with the multi-layer composite structural design, the outward diffusion of Mo elements and the inward diffusion of O elements are suppressed, while ensuring high-temperature wear resistance, the high-temperature thermal stability and oxidation resistance of the coating are improved.
[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0024] (1) The present invention adopts industrial multi-arc ion plating technology, and the film prepared has high hardness. By adjusting the substrate bias voltage proportional coefficient, the bias voltage can be linearly increased, which is conducive to alleviating the high stress inside the coating. The prepared coating has good bonding strength, and the preparation process is simple and easy to operate, which can achieve large-scale production;
[0025] (2) The present invention, by doping Mo and Ta elements of different compositions, combines the high wear resistance of Mo with the high thermal stability and oxidation resistance of Ta, fully utilizing the advantages of multi-component elements, and prepares a series of coatings with different compositions. The prepared coatings not only ensure high hardness, but also have good high-temperature wear resistance and high-temperature oxidation resistance, and are particularly suitable for processing materials at high temperatures;
[0026] (3) The present invention adopts a multi-element and multi-layer design, and its composition breaks through the traditional design concept; at the same time, the typical multi-layer and buffer structure can also improve the matching between the coating and the substrate, which can greatly reduce the internal stress and increase the bonding strength of the coating; its composition combination combines the advantages of different elements; the multi-layer structural design can interrupt the growth of columnar crystals, prevent dislocation movement and crack expansion, thereby increasing the surface hardness; adding a transition layer between the film and the substrate to form an impact-resistant strengthening zone improves the toughness, thereby enhancing the performance of the film. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the XRD pattern of the coating prepared in Example 6 of the present invention;
[0028] Figure 2 is a cross-sectional view of the coating prepared in Example 6 of the present invention;
[0029] Figure 3 Graph showing the hardness of the coatings prepared in Example 6 of the present invention and Comparative Examples 1 to 3;
[0030] Figure 4 Graph showing the bonding force of the coatings prepared in Example 6 of the present invention and Comparative Examples 1 to 3;
[0031] Figure 5 Graph showing the wear rates of the coatings prepared in Example 6 of the present invention and Comparative Examples 1 to 3;
[0032] Figure 6 1 is a graph showing the annealing hardness of the coatings prepared in Example 6 of the present invention and Comparative Examples 1 to 3;
[0033] Figure 7 The graphs are for the oxidation weight gain of the coatings prepared in Example 6 of the present invention and Comparative Examples 1 to 3;
[0034] Figure 8 The figure shows the length of workpieces cut by tools coated with the coatings of Example 6 of the present invention and Comparative Examples 1 to 3 under actual working conditions. DETAILED DESCRIPTION
[0035] The present invention is further described below with reference to specific embodiments and accompanying drawings.
[0036] Example 1: The method for preparing a TiAlMoN / TiAlTaN composite coating for steel processing of the present invention comprises the following steps:
[0037] (1) Diamond grinding fluids with particle sizes of W6, W3, W1, and W0.5 were used to grind and polish the high-speed steel substrate, and ultrasonically cleaned with acetone and ethanol for 15 minutes respectively;
[0038] (2) Place the cleaned high-speed steel substrate on the turret of the multi-arc ion plating machine, set the workpiece turret speed to 2 r / min, start the vacuum program, turn on the mechanical pump, and pump the vacuum to 10 Pa, then start the molecular pump and pump the vacuum to below 0.02 Pa;
[0039] (3) Turn on the heater, set the cavity heating temperature to 450°C, and adjust the heating rate to 100%;
[0040] (4) Turn off the heater, wait until the vacuum in the chamber reaches below 0.03 Pa, turn on the filament power supply, set the bias voltage to 600 V, introduce 50 sccm of argon, maintain the vacuum at 0.3 Pa, set the DC power supply voltage to 40 V and the current to 15 A, and perform glow cleaning on the substrate for 70 min. The whole process is divided into 5 stages;
[0041] (5) Turn on the Ti target, introduce 40 sccm of argon, deposit the Ti bonding layer, set the arc current to 60 A, the bias voltage to 800 V, and the deposition time to 5 min;
[0042] (6) Turn on the Ti target, turn off the argon gas, introduce 300 sccm nitrogen gas, maintain the vacuum degree at 2.6 Pa, deposit the TiN transition layer, set the arc current to 60 A, the bias voltage to 200 V, the duty cycle to 80%, and the deposition time to 10 min;
[0043] (7) Open (TiAl) 1-x Mo x Target and (TiAl) 1-y Ta yThe target material has x = 3%, y = 2%, and an atomic percentage ratio of Ti:Mo of 40%-60%:2%-10%, and an atomic percentage ratio of Ti:Ta of 40%-60%:2%-10%. The target material is vented by perforating the periphery of the evaporation source. The TiAlMo evaporation source flange has four holes, and the TiAlTa evaporation source flange has four holes to improve the uniformity and density of the coating. A nitrogen gas flow of 450 sccm was used to simultaneously deposit TiAlMoN and TiAlTaN layers with an 80% duty cycle. The bias voltage was increased from 20 V to 150 V with a linear increase ratio set to 1. The deposition time was 68 minutes.
[0044] (8) Turn off the TiAlMo target and the TiAlTa target, turn off the nitrogen and the heater, and take them out of the furnace after cooling.
[0045] Example 2: The difference from Example 1 is that in step (7), (TiAl) 1-x Mo x In the target, x=3%, (TiAl) 1-y Ta y Target, y=5%;
[0046] Example 3: The difference from Example 1 is that in step (7), (TiAl) 1-x Mo x In the target, x=3%, (TiAl) 1-y Ta y In the target, y=8%.
[0047] Example 4: The difference from Example 1 is that in step (7), (TiAl) 1-x Mo x In the target, x=7%, (TiAl) 1-y Ta y In the target, y=2%.
[0048] Example 5: The difference from Example 1 is that in step (7), (TiAl) 1-x Mo x In the target, x=7%, (TiAl) 1-y Ta y In the target, y=5%.
[0049] Example 6: The difference from Example 1 is that in step (7), (TiAl) 1-x Mo x In the target, x=7%, (TiAl) 1-y Ta y In the target, y=8%.
[0050] Example 7: The difference from Example 1 is that in step (7), (TiAl) 1-x Mo x In the target, x=12%, (TiAl) 1-y Ta y In the target, y=2%.
[0051] Example 8: The difference from Example 1 is that in step (7), (TiAl) 1-x Mo x In the target, x=12%, (TiAl) 1-y Ta y In the target, y=5%.
[0052] Example 9: The difference from Example 1 is that in step (7), (TiAl) 1-x Mo x In the target, x=12%, (TiAl) 1-y Ta y In the target, y=8%.
[0053] Comparative Example 1: The difference from Example 6 is that the target material is Ti 50 Al 50 alloy target, and the prepared coating is a single-layer TiAlN coating.
[0054] Comparative Example 2: The difference from Example 6 is that the prepared coating is a single-layer TiAlMoN coating.
[0055] Comparative Example 3: The difference from Example 6 is that the prepared coating is a single-layer TiAlTaN coating.
[0056] The present invention adopts industrial multi-arc ion plating equipment to prepare TiAlMoN / TiAlTaN composite coatings with different compositions according to three alloy targets with different Mo contents and three alloy targets with different Ta contents, and characterizes the microstructure, mechanical properties, friction and wear, thermal stability and oxidation resistance of the prepared composite coatings. The test results are shown in Tables 1 and Figures 1-8 .
[0057] Table 1 shows the performance test results of the coatings prepared in Examples 1 to 9
[0058]
[0059] Table 1 summarizes the performance of nine TiAlMoN / TiAlTaN composite coatings with varying Mo and Ta compositions. As can be seen from Table 1, due to the solid solution strengthening effect of the elements, the composite coatings all achieve hardness exceeding 2600 HV and bond strength exceeding 110 N. Compared to single-layer TiAlN coatings, the Mo-doped composite coatings have a lowest friction coefficient of 0.325. The Ta-doped composite coatings exhibit thermal stability and oxidation resistance up to 1100°C, significantly improving both high-temperature wear resistance and heat resistance.
[0060] Figure 1 The XRD pattern of the TiAlMoN / TiAlTaN composite coating prepared in Example 6 shows that the composite coating is primarily composed of c-AlN, c-TiN, and c-TaN, with a preferred orientation at (200). However, no hcp-AlN phase is detected in the coating. Compared to the TiAlN coating peak, its diffraction peak tends to shift to the left. This is because the Mo and Ta atoms with larger atomic radii replace the Al atoms with smaller atomic radii, forming a solid solution in the TiAlN coating.
[0061] Figure 2 This is a cross-sectional view of the TiAlMoN / TiAlTaN composite coating prepared in Example 6. The coating thickness measured in the figure is 3.4 μm. The coating mainly consists of a Ti metal bonding layer, a TiN transition layer, and a TiAlMoN / TiAlTaN functional layer. The cross-sectional morphology is dense, without obvious holes and cracks, and the coating is well bonded to the substrate.
[0062] Figure 3 The hardness of the coatings produced in Example 6 and Comparative Examples 1, 2, and 3 is plotted. The figure shows that by doping the TiAlN coating with 7% Mo and 8% Ta, the coating's hardness reaches over 3000 HV, a 1.7-fold increase compared to the TiAlN coating. This is likely due to the solid solution strengthening effect of the co-doping with Mo and Ta atoms. Furthermore, the interfacial effect between the TiAlMoN and TiAlTaN layers in the nano-multilayer hinders dislocation motion, leading to dislocation pileup at the interface and resulting in increased hardness.
[0063] Figure 4 Figure 6 shows the bonding strength of the coatings in Example 6 of the present invention and Comparative Examples 1, 2, and 3. The figure shows that the composite coating exhibits relatively high bonding strength, significantly improved compared to the single-layer coating. This may be because the hardness of the composite coating is increased after element doping, and the coherent epitaxial growth between the layers has a significant buffering effect on stress, hindering the propagation of cracks into the substrate and ensuring a strong bond between the substrate and the coating.
[0064] Figure 5The wear rate diagram of the coating in Example 6 of the present invention and Comparative Examples 1, 2, and 3 is shown. Under the same test environment, the TiAlMoN / TiAlTaN composite coating exhibits excellent wear resistance. After 100 meters of wear, the wear rate of the TiAlN coating prepared in Comparative Example 1 reaches 1.1×10 -7 mm 3 N -1 m -1 There are white dotted marks on the coating surface, indicating that the coating has been worn through, while the composite coating prepared in Example 6 has 4.3×10 -8 mm 3 N -1 m -1 , indicating that MoO3 has a lubricating effect on the coating.
[0065] Figure 6 The following graph shows the annealing hardness of the coatings in Example 6 of the present invention and Comparative Examples 1, 2, and 3. The coatings were vacuum annealed at 800°C, 900°C, and 1000°C. The composite coating exhibited higher annealing hardness than the single-layer coating at all temperatures, reaching a hardness of 2500 HV at 1000°C.
[0066] Figure 7 Oxidation weight gain curves for the coatings in Example 6 of the present invention and Comparative Examples 1, 2, and 3. The coatings were oxidized in air at 700°C to 1000°C. At 700-800°C, all coatings oxidized slowly. However, at 1000°C, the composite coating exhibited the lowest oxidation weight gain of all coatings, only about half that of the TiAlN coating.
[0067] Figure 8 Figure 2 shows the actual workpiece lengths cut by tools coated with Example 6 and Comparative Examples 1-3 under actual working conditions. At a cutting speed of V = 120 m / min, f = 0.15 mm / r, and ap = 2.0 mm, the TiAlN-coated tool cut 92 m of workpiece when the back face wear reached 0.3 mm. Single-layer TiAlMoN and TiAlTaN coatings cut 119 m and 132 m, respectively, and the composite coating cut 165 m. Compared to the TiAlN coating, tool life was increased by 44%.
Claims
1. A TiAlMoN / TiAlTaN composite coating for steel processing, characterized in that: The composite coating comprises a Ti bonding layer, a TiN transition layer and a TiAlMoN / TiAlTaN functional layer, wherein the TiAlMoN / TiAlTaN functional layer is composed of (TiAl) 1-x Mo x N layer and (TiAl) 1-y Ta y N layer, wherein x: 2-20at.%, y: 2%-15at.%, and x+y: 5%-30at.%. The method for preparing the TiAlMoN / TiAlTaN composite coating for steel processing comprises the following steps: (1) Pretreatment of the substrate; (2) Place the substrate on the rotating rack of the multi-arc ion coating machine and start the vacuuming process; (3) Turn on the heater; (4) Turn on the filament power supply, introduce argon gas, maintain the vacuum degree, set the DC power supply voltage and current to perform glow cleaning on the substrate; (5) Turn on the Ti target, introduce argon, maintain vacuum, and plate the Ti bonding layer; (6) Turn on the Ti target, turn off the argon gas, introduce nitrogen, maintain the vacuum, and plate the TiN transition layer; (7) Open the TiAlMo target and TiAlTa target, introduce nitrogen, and deposit the TiAlMoN layer and TiAlTaN layer simultaneously to plate the TiAlMoN / TiAlTaN functional layer; (8) Turn off the TiAlMo target and the TiAlTa target, turn off the nitrogen and the heater, and take them out of the furnace after cooling to obtain the TiAlMoN / TiAlTaN composite coating for steel processing; In step (7), the parameters of the TiAlMoN / TiAlTaN functional layer are: arc current of 80-120A, duty cycle of 60-90%, bias voltage increased from 10-50V to 100-200V, bias voltage linear increase ratio of 0.5-3, and deposition time of 40-80min.
2. The composite coating according to claim 1, characterized in that The thickness of the Ti bonding layer is 50-100 nm, the thickness of the TiN transition layer is 200-600 nm, and the thickness of the TiAlMoN / TiAlTaN functional layer is 1-6 μm.
3. The composite coating according to claim 1, characterized in that In step (2), the substrate is high-speed steel or cemented carbide; the speed of the rotating rack is 1-4 r / min, and the vacuum degree after vacuuming is (1-5)×10 -2 Pa.
4. The composite coating according to claim 1, characterized in that In step (3), the heating temperature is 300-500°C.
5. The composite coating according to claim 1, characterized in that In step (4), the flow rate of the argon gas is 20-70 sccm, the DC power supply voltage is 30-60 V, the current is 10-20 A, and the glow cleaning time is 30-90 min.
6. The composite coating according to claim 1, characterized in that In step (5), the parameters of the Ti-plated bonding layer are: arc current of 30-50A, bias voltage of 600-800V, and deposition time of 2-6min.
7. The composite coating according to claim 1, characterized in that In step (6), the flow rate of the nitrogen gas is 130-180 sccm; the parameters of the TiN transition layer are: arc current is 40-70 A, duty cycle is 20-80%, bias voltage is 200-300 V, and deposition time is 5-15 min.
8. The composite coating according to claim 1, characterized in that In step (7), in the TiAlMo alloy target and the TiAlTa alloy target, the atomic percentage ratio of Ti:Mo is 40%-60%:2%-10%, and the atomic percentage ratio of Ti:Ta is 40%-60%:2%-10%; the ventilation of the target material is achieved by drilling holes around the evaporation source, wherein the number of holes in the flange of the TiAlMo evaporation source is 3-8, and the number of holes in the flange of the TiAlTa evaporation source is 3-8.
Citation Information
Patent Citations
Multi-layer composite coating for improving cutting speed of circular saw blade
CN107354437A